2012
DOI: 10.1007/s10761-012-0171-4
|View full text |Cite
|
Sign up to set email alerts
|

An Institution that was a Village: Archaeology and Social Life in the Hansen’s Disease Settlement at Kalawao, Moloka‘i, Hawaii

Abstract: Archaeological research in the Hansen's disease settlement at Kalawao, Moloka'i, Hawaii, has revealed evidence that challenges patterns expected from theoretical and archaeological research on total institutions. While written documents provide evidence for a community with many of the classic elements of places of social control, archaeological remains fit better with models of post-contact Hawaiian village life. This apparent contradiction is revealing for the power dynamics produced in the social life of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
4
0
4
Order By: Relevance
“…Our data illustrates that Miloliʻi stone tool assemblages were produced from locally available sources. The EDXRF results also demonstrated that the small bipolar core at Site 7206 was flaked from manufactured glass, probably bottle glass, an activity found at a limited number of historic contexts in the archipelago (Dockall ; Flexner ; Flexner & Morgan ). In addition, the EDXRF analyses documented that one piece of mis‐identified volcanic glass was, in fact, coal, indicating the utility of such analyses for accurately identifying materials in early historic domestic sites.…”
Section: An Overview Of the Miloli‘i Chronology And Inter‐assemblage mentioning
confidence: 84%
“…Our data illustrates that Miloliʻi stone tool assemblages were produced from locally available sources. The EDXRF results also demonstrated that the small bipolar core at Site 7206 was flaked from manufactured glass, probably bottle glass, an activity found at a limited number of historic contexts in the archipelago (Dockall ; Flexner ; Flexner & Morgan ). In addition, the EDXRF analyses documented that one piece of mis‐identified volcanic glass was, in fact, coal, indicating the utility of such analyses for accurately identifying materials in early historic domestic sites.…”
Section: An Overview Of the Miloli‘i Chronology And Inter‐assemblage mentioning
confidence: 84%
“…As pesquisas em arqueologia têm demonstrado que é necessário atentar para o conceito de instituição total, proposto por Goffman, considerando que o cotidiano nos leprosários indica a pluralidade nas relações de poder possíveis (Lopes, 2017;Flexner, 2012;French, 1995). Neste trabalho, utilizarei o conceito no sentido de problematizar as pretensões de controle sobre os doentes, tendo em vista as características da Colônia Santo Antônio do Prata.…”
Section: Saúde Pública E a Lepra No Brasil Republicanounclassified
“…Inglis's interpretation has been corroborated by archaeological research, which concurs with her conclusion that the early settlement of leprosy-affected people on Kalaupapa was very much a Hawaiian village. 81 In the Cook Islands, a policy of isolation explicitly, if loosely, modelled on Molokai was implemented from 1890 to 1925. As Raeburn Lange shows, the islets of banishment in the Cooks were commonly called 'Molokai'.…”
Section: The Collectionmentioning
confidence: 99%